Contrast-enhanced ultrasonography in interventional oncology - Gummadi, Sriharsha (Abdom Radiol (NY), 2018)
Contrast-enhanced ultrasound (CEUS) has evolved from the use of agitated saline to second generation bioengineered microbubbles designed to withstand insonation with limited destruction. While only one of these newer agents is approved by the Food and Drug Administration for use outside echocardiography, interventional radiologists are increasingly finding off-label uses for ultrasound contrast agents. Notably, these agents have an extremely benign safety profile with no hepatic or renal toxicities and no radiation exposure. Alongside diagnostic applications, CEUS has begun to develop its own niche within the realm of interventional oncology. Certainly, the characterization of focal solid organ lesions (such as hepatic and renal lesions) by CEUS has been an important development. However, interventional oncologists are finding that the dynamic and real-time information afforded by CEUS can improve biopsy guidance, ablation therapy, and provide early evidence of tumor viability after locoregional therapy. Even more novel uses of CEUS include lymph node mapping and sentinel lymph node localization. Critical areas of research still exist. The purpose of this article is to provide a narrative review of the emerging roles of CEUS in interventional oncology.